Comparative study between Buprenorphine and Fentanyl transdermal patch to evaluate post-operative pain relief after cardiac surgery: A randomized control trial study - Vijay Harischandra Patil; Bhagyashree Inkane; Dipakkumar Hiralal Ruparel; Subin Thomas (International Journal of Health and Clinical Research, 2022)
Introduction: Pain due to thoracotomy creates greatest demand for postoperative analgesia. Multimodal analgesia with various routes can be of great help to fulfill demands of analgesia in these patients. Opioids given by transdermal route offers newer modality of management with potential benefits of being noninvasive, sustained blood levels and bypasses first pass metabolism. We aimed to evaluate efficacy of Buprenorphine and Fentanyl Transdermal patch for post-operative pain relief after cardiac surgery. Methods: It was prospective, randomized, double-blind study in which 60 adult patients undergoing cardiac surgery were randomly segregated into two groups. Group A: 30 patients received Buprenorphine transdermal patch (10mcg/hr) and Group B: 30 patients received Fentanyl transdermal patch (50mcg/hr) 12- 24 hours prior to extubation. Analgesia was assessed using VAS score along with hemodynamic parameters and adverse effects. Results: Demographic parameters, baseline hemodynamics and perioperative hemodynamics were comparable. Baseline VAS score was comparable in two groups however statistically significant difference in two groups in VAS was observed thereafter till 72 hours. VAS score was higher in group A as compared to group B at the time of removal of ICD. 3 (10%) and 2 (6.7%) patients in Group A and Group B respectively required rescue analgesic which was not significant. Time for requirement of first rescue analgesic was significantly longer in Group B compared to Group A ie767.13 ± 73.59 minutes vs. 1224.37 ± 39.37 minutes. Adverse effects were comparable in two groups. Conclusion: Fentanyl and Buprenorphine TDDS are effective in postoperative analgesia in cardiac surgical patients. However Fentanyl TDDS has better analgesia.